KOMBINASI LATIHAN BUERGER ALLEN DAN LATIHAN BERJALAN EFEKTIF MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Hidayati, Ratna; Widayati, Dhina; Yunaeni, Helmia Natasha (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Hypertension or high blood pressure that occurs continuously can damage blood vessels and complications in the kidneys. One of the hypertension management to lower blood pressure can be done with exercise. The combination of Buerger Allen exercise and walking exercise is a form of exercise method. The purpose of this study was to determine the effect of the combination of Buerger Allen exercise and walking exercise on blood pressure in hypertension patients in Sumberbendo Village, Pucanglaban District. The research design was pre-experimental design with a one group pretest-posttest without control approach. The sampling technique used purposive sampling, 36 respondents were obtained from 115 populations. The dependent variable in this study was blood pressure. The instrument in this study used a blood pressure observation sheet. Statistical analysis used the Paired T-Test with α 0.05. The results of the study before being given the intervention of a combination of Buerger Allen exercise and walking exercise, most (61.1%) respondents experienced stage 1 hypertension, and after the intervention, most (72.2%) respondents experienced pre-hypertension. The results of statistical analysis obtained systolic blood pressure p-value = 0.001, diastolic blood pressure p-value = 0.001 (≤ α 0.05), so there is an effect of the combination of Buerger exercises and walking exercises can lower blood pressure. The combination of Buerger Allen exercises and walking exercises has a mechanism to help muscle pump (pumping blood into blood vessels) and vasodilation of blood vessels which will make blood circulation smooth and peripheral retention decreases so that systolic and diastolic blood pressure decreases. The combination of Buerger Allen exercises and walking exercises can be used as one of the hypertension management with physical activity to lower blood pressure.